2020
DOI: 10.1080/09540105.2020.1826911
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy to shrimps and fish in patients suffering from atopic dermatitis, the results of ISAC Multiplex examination

Abstract: The aim of this study is the evaluation of the occurrence of fish/ shrimp allergy in atopic dermatitis patients. The occurrence of fish/shrimp allergy was confirmed in the challenge test or according to the history; the sensitisation to molecular components with ISAC Multiplex testing was analysed. Altogether 100 atopic dermatitis patients were examined. The food allergy to fish was confirmed in 13 patients (13%), while shrimp allergy occurred in 6 patients (6%).In patients with allergy to fish, the significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…We report here the most likely allergens forming the underlying molecular basis for this not well-understood clinical phenomenon. Furthermore, the current study, for the first time, identified allergens that are possibly responsible for clinical cross-reactivity between shrimp and fish [25]. Beta-enolase and aldolase A, enzymatic proteins of the glycolytic pathway, were identified as heat labile allergens in various fish species and chicken [15,76,77].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We report here the most likely allergens forming the underlying molecular basis for this not well-understood clinical phenomenon. Furthermore, the current study, for the first time, identified allergens that are possibly responsible for clinical cross-reactivity between shrimp and fish [25]. Beta-enolase and aldolase A, enzymatic proteins of the glycolytic pathway, were identified as heat labile allergens in various fish species and chicken [15,76,77].…”
Section: Discussionmentioning
confidence: 74%
“…These two allergens were not included in the main results of this study as they were identified from plant and fungi species (Triticum aestivum and Aspergillus fumigatus) that are phylogenetically distant to shrimps. However, there is emerging evidence of patients suffering from shrimp allergy also being sensitised to plant and fungi allergens [25,26]. The allergen cyclophilin is generally found in dust mite, fungi and plants, and demonstrates strong IgE-binding [63,78].…”
Section: Discussionmentioning
confidence: 99%